O społecznościach lokalnych i wspólnotach ludzkich w warunkach globalizacji – perspektywa pedagogiczna - Segiet, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2020)
Contemporary researchers of local communities and human societies face a new and difficult task today. It is, on the one hand, related to the great interest in this topic and the difficulty of creating a new concept that would fully exhaust the scope of phenomena observed presently in local communities and human societies. On the other hand, the character of changes that have gained momentum in the first decade of the 21st century, and the description of their sources, become particularly difficult to describe and name. The present article is an attempt at an indication of the need of an evolution of perception on societal reality and the emerging new social issues. Contemporary paedagogy attempts to write about the necessity of awareness/ education related to the needs of establishment of local communities and the creation of bonds as a response to processes related to social life in times of globalisation. It is a fact that we are presently dealing with a change in the forms and character of local communities.